Growth and wetting of water droplet condensed between micron-sized particles and substrate - Quang, Tran Si Bui (2018)
We study heterogeneous condensation growth of water droplets on micron-sized particles resting on a level substrate. Through numerical simulations on equilibrium droplet profiles, we find multiple wetting states towards complete wetting of the particle. Specifically, a partially wetting droplet could undergo a spontaneous transition to complete wetting during condensation growth, for contact angles above a threshold minimum. In addition, we find a competitive wetting behavior between the particle and the substrate, and interestingly, a reversal of the wetting dependence on contact angles during late stages of droplet growth. Using quasi-steady assumption, we simulate a growing droplet under a constant condensation flux, and the results are in good agreement with our experimental observations. As a geometric approximation for particle clusters, we propose and validate a pancake model, and with it, show that a particle cluster has greater wetting tendency compared to a single particle. Together, our results indicate a strong interplay between contact angle, capillarity and geometry during condensation growth.